Serial testing of latent tuberculosis infection in patients with diabetes mellitus using interferon-gamma release assay, tuberculin skin test, and creation tuberculin skin test - Yijun He; Xuefang Cao; Tonglei Guo; Yongpeng He; Ying Du; Haoran Zhang; Boxuan Feng; Jiang Du; Bin Zhang; Kun Wang; Jiaoxia Yan; Dakuan Wang; et al. (Frontiers Media S.A., 2022)
BackgroundDiabetes mellitus (DM) patients with latent tuberculosis infection (LTBI) have an increased risk of developing active tuberculosis (TB) due to impaired immunity. The performance of currently available immune response-based assays for identification of TB infection had been rarely evaluated in patients with type 2 DM (T2DM) in China.MethodsA prospective study was conducted to investigate the status of LTBI in patients with confirmed T2DM. At the baseline survey, the prevalence of LTBI was tested using interferon-gamma release assay (IGRA), tuberculin skin test (TST) and creation tuberculin skin test (C-TST) in parallel. After a 3-month interval, the participants were retested by the three assays to estimate their performance in the serial testing.ResultsA total of 404 participants with T2DM were included in the study. At baseline, after excluding active TB, the prevalence of LTBI identified by TST (≥ 10 mm), C-TST (≥ 5 mm) and IGRA (≥ 0.35 IU/ml) were 9.65% (39/404), 10.40% (42/404) and 14.85% (60/404), respectively. The concordance of TST and C-TST results with IGRA results was 86.39% (349/404) and 92.08% (372/404) with a Kappa coefficient of 0.37 [95% confidence interval (CI): 0.24- 0.50] and 0.64 (95% CI: 0.53- 0.76), respectively. After a 3-month interval, the continuous results of TST, C-TST and IGRA were observed to be increased with testing conversion for 50, 26 and 27 patients, respectively. For TST and C-TST conversions, the distribution of their quantitative results in serial tests varied significantly when further classified by baseline IGRA dichotomous results.ConclusionIn studied patients with T2DM, C-TST showed higher consistency with IGRA as compared to TST. The present of conversion observed in serial testing suggested that boosting effect of skin testing should be considered for identify of LTBI in patients with T2DM.